The position of the Spanish monarchy and Catalan separatism in the 21st century - Husar-Poliszuk, Wioletta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the position of the Spanish monarchy in the context of Catalan separatism (independentism). The analysis is focused on the search for potential relationships between the weakening position of the Spanish monarchy and Catalan independentism and the consequences associated with this. To this end, the exploration includes both the monarchy in the institutional sense and focuses on the person of Juan Carlos I de Burbon himself and his son and successor Philip VI de Burbon.
Keywords: Catalan separatism; Catalan independentism; Spanish monarchy; Juan Carlos I Alfonso Víctor María de Borbón y Borbón-Dos Sicilias (król Hiszpanii; 1938- ); Philippe VI de Burbon (król Hiszpanii; 1968- )